The Use of Euphemisms in the Book of â€œThe Alchemistâ€ by Paulo Coelho - Tarigan, Smirna Br; Marpaung, Marlin Steffi (JOLLT Journal of Languages and Language Teaching, 2023)
Euphemisms are a linguistic phenomenon whereby milder or courteous words are substituted for blunt or unpleasant expressions. This study focuses on the use of euphemisms and related expressions in Paulo Coelho's book, "The Alchemist." Specifically, the research aims to identify the various euphemistic devices employed, ascertain the prevalence of such devices, and explicate their significance within the context of the novel. A descriptive qualitative research design was employed, which involved an in-depth and detailed exploration and analysis of the phenomena under investigation. To obtain the necessary data, a comprehensive review of relevant literature and library resources was conducted. The results revealed that Paulo Coelho's "The Alchemist" contains several euphemisms that serve to enhance the overall tone and mood of the narrative. The study further identified four distinct types of euphemisms in the novel, namely euphemisms used to soften descriptions of physical attributes, mental states, skills, etc., euphemisms used to make disagreeable situations more palatable, euphemisms used in business contexts, and euphemisms used in other contexts. Of these categories, the most common type, accounting for 44.5% of all instances, was found to be euphemisms used to make something sound more pleasant.